2010
DOI: 10.1017/s1742058x10000275
|View full text |Cite
|
Sign up to set email alerts
|

Articulating a Politics of (Multiple) Identities

Abstract: This work examines the strategies Black lesbian, gay, bisexual, and transgender (LGBT) people use in Black environments to proclaim a gay identity that is simultaneous with a Black identity. It identifies three distinctive features of LGBT protest in Black communities. Black gay2 protest takes on a particular form when individuals are also trying to maintain solidarity with the racial group despite the threat of distancing that occurs as a result of their sexual minority status. Black sexual minorities who see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 17 publications
0
23
1
Order By: Relevance
“…One such pathway is believed to operate via one’s shared stigmatized identity (i.e., race/ethnicity) with similar others, which may provide sexual minority individuals of color with protective early learning environments that offer stigma-related coping skills and supportive community resources (Greene, 1994; Saleebey, 1996; Shih, 2004). Subsequently, sexual minority individuals of color may adapt and use these skills to cope with sexual orientation-based minority stress (e.g., Bowleg, Huang, Brooks, Black, & Burkholder, 2003; Meyer, 2015; Moore, 2010), resulting in fewer adverse health outcomes for sexual minority individuals of color, like those observed in the present study.…”
Section: Discussionmentioning
confidence: 61%
“…One such pathway is believed to operate via one’s shared stigmatized identity (i.e., race/ethnicity) with similar others, which may provide sexual minority individuals of color with protective early learning environments that offer stigma-related coping skills and supportive community resources (Greene, 1994; Saleebey, 1996; Shih, 2004). Subsequently, sexual minority individuals of color may adapt and use these skills to cope with sexual orientation-based minority stress (e.g., Bowleg, Huang, Brooks, Black, & Burkholder, 2003; Meyer, 2015; Moore, 2010), resulting in fewer adverse health outcomes for sexual minority individuals of color, like those observed in the present study.…”
Section: Discussionmentioning
confidence: 61%
“…It is plausible that participants referred to the LGBT community with which they are most familiar, which, of course, should not be assumed to be a White LGBT community. For example, recent research has demonstrated that sexual minorities of color can have strong racial/ethnic and sexual identities (Meyer & Ouellette, 2009; Moore, 2010; Stirratt, Meyer, Ouellette, & Gara, 2008), suggesting the ability to feel connected to sexual minority communities that include and are inclusive of people of color. Findings of no difference in connectedness based on race/ethnicity may also be related to the fact that New York City has historically well-established sexual minority communities of color (Hawkeswood, 1996; Silberman, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Racial/ethnic minorities may feel invisible and marginalized, and are often subject to racism in White LGBT communities (Binnie & Skeggs, 2004; Han, 2007). Therefore, it is important to note that term LGBT community as we use it should not be understood as referring to one (White) community but as referring to the diversity of LGBT communities (Meyer & Ouellette, 2009; Moore, 2010). This allows consideration of differences among subgroups of sexual minority individuals, but does not presume that only White sexual minority people have a community.…”
Section: Diversity In Connectedness To the Lgbt Communitymentioning
confidence: 99%
“…The unique position of black churches as more than a source of worship (Lincoln and Mamiya 1990, Jones and Hill 2002, Barnes 2005) makes it particularly difficult to leave -even when people leave, they are still influenced by the Black Church (Dyson 2003, Hill 2013. Another way race matters is that black LGBTQ people live in black communities instead of 'gay neighborhoods', which are usually white (Moore 2010, Moore 2011a, Dudley 2013, and leaving means breaking ties that alleviate racism (Johnson 2001, Bowleg et al 2008, Bridges, Selvidge and Matthews 2003. When non-religious paths lead to LGBTQ spaces, these spaces tend to be largely white (Han 2007, Han 2008, Dudley 2013) and black LGBTQ people encounter racism and discrimination (Loiacano 1993, Jones and Hill 1996, Battle et al 2002, Gonzales Ruddell-Tabisola 2009.…”
Section: Non-religion Communities and Spacementioning
confidence: 99%